PENGARUH KEDISIPLINAN DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA PT. TIMUR DELI WICAKSANA. - Eka Sartika Sinaga; Sinditia Sinditia; Desy Natasya Bleszynsky Sinambela; Santo Leonardo Sinaga (JURNAL GLOBAL MANAJEMEN, 2019)
This research was conducted to find out the effect of the discipline and communication on the employees’ performance in P.T. Timur Deli Wicaksana located on Jln. Prof H.M. Yamin No. 86 Medan. The population in this study was thirty (30) persons from the sample of ninety eight (98) persons. Quantitative approach was used in conducting this research. The research also applied descriptive research method, the nature of causal research and multiple linear regression analysis method. Research findings showed simultaneously that communication and discipline had positive and significant effect on employees’ performance (18.382>2,31) with a significant level of 0.000 <0.05). Partially discipline positively and significantly affected employee performance (value t> t table (2,754>1,66055and significant values> 0.05). Partially communication had positive and significant effect on employees’ performance (value t> t table (3.985>1,66055) and significant values> 0.05).